Transglycosylation, a new role for multifunctional cellulase in overcoming product inhibition during the cellulose hydrolysis. Issue 2 (4th March 2017) - Wang, Xu; Wu, Yanbo; Zhou, Yu
ABSTRACT: Cellulase mainly consisting of exo-glucanase, endo-glucanase and β-glucosidase, was considered as the most important biocatalyst for bioconversion of ethanol and other biofuels, feedstuffs and pharmaceuticals. Hydrolysis product inhibition, especially of glucose inhibition, is one of the critical difficulty awaiting to be overcome during cellulose bioconversion. Recently, several studies showed that some multifunctional cellulases (e.g., Umcel9y-1, Td2F2 and CoGH1A) could eliminate or relieve the product inhibition through transglycosylation actions during the cellulose hydrolysis. Transglycosylation confers multifunctional cellulases insensitive character to the end products (glucose and/or cellobiose), and provides a potential access in overcoming the inhibition of biofuels conversion. Moreover, transglycosylation harboring cellulases are also attracted as substitute of glycosyltransferase in synthesis of functional foods, nutraceuticals, or pharmaceuticals. Here, several interested transglycosylation harboring cellulases were summarized and assessed for the potential values in bioengineering application.